Drug safety: focus on long-term therapy with proton pump inhibitors. Possible side effects - Dmitry I. Trukhan (LLC "MEDIAFORMAT", 2024)
Proton pump inhibitors (PPIs) are the most effective drugs for the treatment of acid-related diseases. For a long time, PPIs were considered completely safe drugs for both short-term and long-term use. However, modern clinical guidelines note that when prescribing PPIs in large doses for a long period, the possibility of side effects should be taken into account. In a clinical context, a reasonable definition of long-term PPI use would be PPI use for more than 8 weeks in patients with symptoms of gastroesophageal reflux disease and more than 4 weeks in patients with peptic ulcers or functional dyspepsia. There are no reviews in the domestic literature on the safety of PPIs during long-term use. In this regard, a search was conducted in the PubMed and Scopus information databases for publications on the safety of PPI use, including sources up to November 15, 2023, which showed that long-term use of PPIs is associated with the possible development of numerous side effects. The first publication examined the possible side effects of long-term use of PPIs: the development of infections, an increased risk of fractures and kidney pathology. This review examines the most possible side effects associated with long-term PPI therapy: the development of cancer and electrolyte disturbances. If there are indications for long-term use of PPIs in accordance with clinical guidelines (Barrett's esophagus, erosive esophagitis C/D and a number of others), oncological vigilance should be exercised and monitoring aimed at identifying electrolyte disturbances should be carried out.